ANALYSIS OF THE EFFECT OF ISLAMIC BANK INCOME AND INCOME CONVENTIONAL BANKS AGAINST BANK PROFITABILITY - Erwin SP, Muhammad; Siregar, Saparuddin; Sugianto, Sugianto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Bank Syariah Indonesia has sharia contracts that can make it easier for customers to get consumptive financing such as financing in the purchase of cars/motorcycles, but many people do not know that Islamic banks have such consumptive financing products. Based on the results of research on the mechanism and application of consumptive financing on the Oto iB Hasanah BNI Syariah Banda Aceh product, this can be done in three stages, namely: First, the customer applies for consumptive financing for the Oto iB Hasanah BNI Syariah Banda Aceh product by completing the file, second, checking data or verifying data for completeness and the truth of the file, thirdly, a field survey with the 5C principle (Character, Capacity, Capital, Condition and Collateral). murabahah namely an agreement on profit, payment method, sale and purchase agreement and delivery of goods.